Adolescent‘s future orientations: Gender differences - Sondaitė, Jolanta (Psichologija, 2001)
This study examines gender differences in future goals, hopes, fears and strategies. The subjecs are 298 adolescents of the age 14-17. Methods used are Future Hopes and Fears Questionnaire and the Strategy and Attribution Questionnaire. The results showed significant differences between boys and girls future hopes and especially fears. The girls more often than boys included education in their hopes for the future. The boys more frequently than girls included property-related issues in their hopes for the future. The results further showed that girls mentioned more frequently concerns and feares related to education, marriage/family, friends, relationship to parents and other things compared to boys. The girls apply more often than boys seeking social support, reflective thinking, master orientation in an achievement situation and success expectation, master-orientation and pessimism in an affiliative context.